ИНГЛИС ҲӘМ ҚАРАҚАЛПАҚ ТИЛИНДЕ GENDER/ЖЫНЫС (ЕР -ҲАЯЛ) ТҮСИНИКЛЕРИНИҢ ГРАММАТИКАЛЫҚ ҲӘМ ЛЕКСИКА - СЕМАНТИКАЛЫҚ БИЛДИРИЛИЎИ - Курбанбаева, Д.М. (FAN va JAMIYAT, 2019)
The article deals with gender distinction of nouns as a part of speech in the English and Karakalpak languages. The problem of gender distinction, as the author points out, is one of the complicated problems in both languages, and though the languages are represintatives of different families, the researcher finds out the ways of distinguishing gender of nouns in these languages and gains to systematize them in proper scientific way.